Success Rate Of Hatching Of Green Turtle Eggs ( Chelonia Mydas) On Bangkaru Island, Banyak Island, Aceh Singkil - Alaudin, Alaudin; Burhanis, Burhanis; Okasari, Rafika; Bahri , Samsul; Kamba, Ria (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
Turtles are biota that are included in the protected animal category because they have a high level of threat of extinction due to natural and anthropogenic factors. Turtles spend their time in the open sea and go ashore to lay their eggs each season. The successful hatching of turtle eggs is important as an effort to increase their population. This research aims to see the success rate of hatching of green turtle (Chelonia Mydas) eggs on Bangkaru Island, Banyak Island, Aceh Singkil. This research was carried out from March to June 2024. The research was carried out by observing at the green turtle nesting beach the number of nests, number of eggs, nest meters, percentage of hatched eggs. The method used in this research is a survey (direct observation). In the results of research that has been carried out, the highest percentage of turtle eggs is found in the 6th nest with a percentage of 48%, while the lowest percentage is found in nests 1, 2 and 4 with a percentage of 0%. The high percentage in the 6th nest is estimated because of the location. nest that is suitable for the nest, because the nest is directly exposed to the sun and is far from the ebb and flow of sea water which results in the nest being damp and the temperature of the nest remaining stable, the low hatching rate in nests 1, 2, and 4 is because the nest is close to the nest. The ebb and flow of sea water causes the nest to be flooded with sea water and the nest is not exposed to enough sunlight, which causes the eggs to rot in the nest.